2011
DOI: 10.1002/ejoc.201101102
|View full text |Cite
|
Sign up to set email alerts
|

Methyl 2‐Furoate: An Alternative Reagent to Furan for Palladium‐Catalysed Direct Arylation

Abstract: International audienceThe palladium-catalysed direct arylation of methyl 2-furoate with aryl bromides was studied. The use of KOAc as the base, dimethylacetamide (DMAc) as the solvent and Pd(OAc)2 as the catalyst was found to give 5-arylfurans regioselectively and without decarboxylation. These methyl 5-aryl-2-furoates gave 2,5-diarylfurans by decarboxylative coupling by using Pd(OAc)2 as the catalyst. Methyl 2-furoate thus represents a convenient alternative substrate to furan for the synthesis of mono- or po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
33
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 58 publications
2
33
0
Order By: Relevance
“…[37] More recently, Doucet and co-workers reported that the PdA C H T U N G T R E N N U N G (OAc) 2 -catalyzed reaction of furans 6 and 8 with 3-iodoaniline under ligandless conditions gave the 5-arylated furans 24a and 24b in 31 and 56% yields, respectively (Scheme 10). [31] They also found that the reaction between 8 and 2-iodo-4-trifluoromethylaniline under the reaction conditions reported in Scheme 10 gave methyl 5-(2-amino-5-trifluoromethylphenyl)-2-methylfuran-3-carboxylate (25) (Figure 4) in 61% yield. [31] Interestingly, the reaction conditions employed to prepare compounds 24a, 24b and 25 proved also suitable for the C-5 arylation of 2-substituted thiophenes 13, 2-substituted thiazoles 14 and 1-methyl-2-acetylpyrrole (26) as well as for the C-4 arylation of 3,5-di-A C H T U N G T R E N N U N G substituted isoxazoles 27 ( Figure 5) and in no case was the formation of amination products detected.…”
Section: A C H T U N G T R E N N U N G (Hetero)arylation Of Furan Andmentioning
confidence: 95%
See 4 more Smart Citations
“…[37] More recently, Doucet and co-workers reported that the PdA C H T U N G T R E N N U N G (OAc) 2 -catalyzed reaction of furans 6 and 8 with 3-iodoaniline under ligandless conditions gave the 5-arylated furans 24a and 24b in 31 and 56% yields, respectively (Scheme 10). [31] They also found that the reaction between 8 and 2-iodo-4-trifluoromethylaniline under the reaction conditions reported in Scheme 10 gave methyl 5-(2-amino-5-trifluoromethylphenyl)-2-methylfuran-3-carboxylate (25) (Figure 4) in 61% yield. [31] Interestingly, the reaction conditions employed to prepare compounds 24a, 24b and 25 proved also suitable for the C-5 arylation of 2-substituted thiophenes 13, 2-substituted thiazoles 14 and 1-methyl-2-acetylpyrrole (26) as well as for the C-4 arylation of 3,5-di-A C H T U N G T R E N N U N G substituted isoxazoles 27 ( Figure 5) and in no case was the formation of amination products detected.…”
Section: A C H T U N G T R E N N U N G (Hetero)arylation Of Furan Andmentioning
confidence: 95%
“…[25] It was also found that reaction conditions similar to those used to prepare compounds 31a-g enabled the C-5 direct arylation of 7g with a large variety of meta-and ortho-substituted aryl bromides in yields ranging from 40 to 80%. [25] Nevertheless, PdA C H T U N G T R E N N U N G (OAc) 2 was found to be an inefficient catalyst precursor for the arylation of 7g with 1-bromo-4-(tert-butyl)benzene, 4-bromotoluene and 4-bromoanisole and satisfactory yields (58-63%) of the reactions involving these electrophiles were obtained using 1 mol% PdClA C H T U N G T R E N N U N G (C 3 H 5 )A C H T U N G T R E N N U N G (dppb) as the catalyst. [25] It was also demonstrated that the PdA C H T U N G T R E N N U N G (OAc) 2 -catalyzed reaction of 1.25 equiv.…”
Section: A C H T U N G T R E N N U N G (Hetero)arylation Of Furan Andmentioning
confidence: 97%
See 3 more Smart Citations